2012
DOI: 10.7314/apjcp.2012.13.7.3335
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Gastric Cancer Incidence in Iran and Its Six Geographical Areas During 2000-2005

Abstract: Objective: gastric cancer is the fourth most common cancer worldwide . While it is one of the most common cancers in Iran, there are only limited data regarding incidence trends in the country. This study is the first of its type to investigate trends across six geographical areas during 2000-2005 using cancer registry data. Materials and methods: The registered data for gastric cancer cases in National Cancer Registry System were extracted from the Ministry of Health and Medical Education, Center for Disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The standardized incidence during the 15 years period showed great fluctuations but overall, there was a decreasing trend from 10.6/10 5 (95%CI: 8.2-13.9) in 1993 to 9.1/10 5 (95%CI: 7.4-11.1) in 2007 (Najafi et al, 2011) (Haidari et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The standardized incidence during the 15 years period showed great fluctuations but overall, there was a decreasing trend from 10.6/10 5 (95%CI: 8.2-13.9) in 1993 to 9.1/10 5 (95%CI: 7.4-11.1) in 2007 (Najafi et al, 2011) (Haidari et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Reports from different parts of the world revealed very different results, but a higher incidence of gastric cancer in males compared to females is common (7).…”
Section: Introductionmentioning
confidence: 95%
“…Compared to China, there has been a more rapid decline in H pylori infection especially in young people in Japan (Lin et al, 2011). Iran is a high risk area for gastric cancer and incidence rates for gastric cancer are increasing, and incidence rates are higher in men than in women (Haidari et al, 2012). Similarly, studies from Pakistan have also demonstrated a rising incidence of gastric cancer, with a male preponderance and mean ages of 51.9 years and 48.8 in males and females respectively.…”
Section: Discussionmentioning
confidence: 92%